PERANCANGAN LOGO PT. LIMA JAYA FARMATAMA PADANG - ANDHIKA HERLANDA, Drs. Syafwan, M.Si, Drs. M. Nasrul Kamal, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
PT. Lima Jaya Fartamatama first established in 1999. It was led by a lady named Bustami Boer. At first, it was located in Gurun Laweh Padang. However, it moved to H. Djuanda number 3A Padang in 2000. It has been centered there since then. Formerly, this company did not just start distributing medicine massively. Neverthelles, this company has been entrusted to be a big pharmaceutical company ' PBF tiga belas'. Additionally, the most boarding industrial companies in indonesia are industri farmasi Ipar, Erita, Polifarma, Novarim, Promat, Uva Pyridam Pisdifarma... Kalbefarma.PBF PT Lima jaya farmatama has been relying heavily on its sales men in respect to convincing the source target to reserve any products of PT Lima jaya farmatama.However, the logo of PT Lima Jaya Farmatam is simply a logotype on which its name is writtenMoreover, PT. Lima Jaya Farmatama does not fulfill the suited logo criterion for this company yet. That PT Lima Jaya Farmatama has been a nationally boarding company in west sumatera is a cause of that. Besides, that this company is entrusted to be a distributor for thirteen nationally pharmaceutical producings.Keyword : Company Identity, Logo, PT. Lima Jaya Farmatama.